Educação musical, relações étnico-raciais e decoloneidade: tensões, perspectivas e interações para a Educação Básica (Orfeu, 2018)
This article points out tensions and approaches perspectives and interactions for decolonization in the field of Music Education, focusing on Basic Education, passing through the debate about Ethnic-Racial Relations Education for the teaching of Afro-Brazilian and African History and Culture. The text points to silences and invisibilities caused by the epistemicides present in curricula and pedagogical-musical practices, given by a Negrocide and presents epistemological perspectives and curricular interactions, for a pedagogical-musical action another. The article focuses on subjectivist research, covering the theoretical field based on political-epistemological and legislative perspectives, in dialogue with the voices of authors and authors that I invite to discuss the theme. I propose a path disobedient to the hegemonic actions established by the structures of patriarchalism, capitalism and colonialism, impregnated and institutionalized, in society that subalternizes, silences and invisibilizes the idea of emancipatory educational project, seen from a pedagogical-musical scope.
Keywords: basic education; curriculum; decoloneity; racial ethnic relations; musical education